BMI1, The polycomb‐group gene, is recurrently targeted by genomic rearrangements in progressive B‐cell leukemia/lymphoma. Issue 10 (19th July 2013) - Rouhigharabaei, Leila; Ferreiro, Julio Finalet; Put, Natalie; Michaux, Lucienne; Tousseyn, Thomas; Lefebvre, Christine; Gardiner, Anne; De, Wim; Demuynck, Hilde; Verschuere, Johan; Théate, Ivan; Vicente, Carmen; et al.
<x xml:space="preserve">Abstract</x> BMI1, a Polycomb‐group gene located at 10p12.2, is implicated in the pathogenesis of a variety of tumors. However, the genetic molecular mechanisms underlying its aberrant expression in cancer cells remain largely unknown. In this study, we show that BMI1 is recurrently targeted by chromosomal aberrations in B‐cell leukemia/lymphoma. We identified a novel t(10;14)(p12;q32)/IGH‐BMI1 rearrangement and its IGL variant in six cases of chronic lymphocytic leukemia (CLL) and found that these aberrations were consistently acquired at time of disease progression and high grade transformation of leukemia (Richter syndrome). The IG‐BMI1 translocations were not associated with any particular molecular subtype of CLL and the leukemias were negative for common mutations of NOTCH1 and TP53, known to increase a risk of progression and transformation in CLL. In addition, using FISH and SNP array analysis, we identified a wide range of BMI1‐involving 10p12 lesions in 17 cases of mantle cell lymphoma (MCL). These aberrations included various balanced and unbalanced structural abnormalities and very frequently but not exclusively, were associated with gain of the BMI1 locus and loss of the 10p terminal sequences. These findings point to genomic instability at the 10p region in MCL which likely promotes rearrangements and deregulation of BMI1. Our findings are in line with previously published observations correlating overexpression of BMI1 with tumor progression and chemoresistance. In summary, our study provides new insights into genetic molecular mechanisms underlying aberrant expression of BMI1 in lymphoma and documents its contribution in the pathogenesis of Richter syndrome and MCL. © 2013 Wiley Periodicals, Inc.